2012
DOI: 10.5811/westjem.2011.6.6679
|View full text |Cite
|
Sign up to set email alerts
|

Family History is a Predictor for Appendicitis in Adults in the Emergency Department

Abstract: Introduction:A family history of appendicitis has been reported to increase the likelihood of the diagnosis in children and in a retrospective study of adults. We compare positive family history with the diagnosis of acute appendicitis in a prospective sample of adults.Methods:We conducted a prospective observational study of a convenience sample of 428 patients. We compared patients with surgically proven appendicitis to a group without appendicitis. The latter were further grouped by their presenting symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In the present study, demographic data represents that male were predominant than females patients. This result is in accordance with already published data which also stated that males were dominant in their studies 15,16 . Moreover, patients had negative female history regarding appendicitis.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, demographic data represents that male were predominant than females patients. This result is in accordance with already published data which also stated that males were dominant in their studies 15,16 . Moreover, patients had negative female history regarding appendicitis.…”
Section: Discussionsupporting
confidence: 94%
“…Drescher et al concluded similarly in adult population 30. When concerning inborn immunity and response to local inflammatory process, Rivera-Chavez et al  demonstrated an association between a polymorphism on a single nucleotide in the interleukin 6 (IL-6) gene (locus IL-6 −174 allele C) and a lower risk of uncomplicated appendicitis 31…”
Section: Discussionmentioning
confidence: 96%
“…Familial aggregation of acute appendicitis has been described in several institutional series and even national registries 2 12–17. These studies have shown that the relative risk of appendicitis increases with a family history of appendicitis,2 and that this risk is inversely related to genetic distance 13.…”
Section: Discussionmentioning
confidence: 97%